Juridicity of Oil and Gas Management in Indonesia as State Control Right (HMN) - Nurharsyah Hanafie; Hasnawi Haris; Herman; Andi Aco Agus (Technium Social Sciences Journal, 2023)
The writing intends and aims as study material to find out the constitutional basis of oil and gas natural resources which are important and strategic for the right to control the state (HMN) for the greatest prosperity and welfare of the people. Materials and data in this writing were obtained both from the 1945 Constitution, the Oil and Gas Law, and other organic regulations relating to Oil and Gas, Oil and Gas Data in the relevant Ministries. Materials and data were also obtained through reference searches or literature that has relevance to this writing, namely in the form of books and laws and regulations related to the issues raised in this writing. Based on the results of material processing and data tracing of laws and regulations, policies, and references that are relevant to this writing, it is obtained, (1) the state’s right to control oil and gas as an important resource and strategy for major contributions to the state budget, national development, and livelihood people.